Linking Religious Awareness of Madrasah Teachers with Critical Thinking - Rohmat Mulyana (Ta'dib: Jurnal Pendidikan Islam, 2023)
This study aimed to obtain an overview of the critical thinking skills and religious awareness of madrasah teachers through three aspects: (1) the transcendental relationship of teachers, (2) teacher religious participation, and (3) the intensity of the teacher’s religious intellect. In addition, the study also attempted to analyze the relationship of critical thinking skills with transcendental relationships, religious participation, and the intensity of teachers’ religious intellectuality. Quantitative research with correlational study was conducted. This study used a stratified random sampling technique. It took 20 to 27 teachers randomly from each madrasah based on the proportion of the number of teachers in each madrasa so that the number of samples reached 154 teachers in Bandung Regency who teach at the Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah. The data collection techniques of the study were test and questionnaire. The results revealed that there was a significant correlational relationship between aspects of critical thinking and three aspects of religious awareness: transcendental relationships, religious participation, and religious intellectuality. The quality of the relationship varies with the highest significance being the relationship between critical thinking and religious intellectuality, followed by transcendental relationships and religious participation.